2012
DOI: 10.4415/ann_12_02_12
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external factors in professional burnout of substance abuse counsellors in Croatia

Abstract: Abstract. aim. In this study, burnout and its internal and external factors were investigated among substance abuse counsellors (no. = 68) who worked in centres for Prevention and Substance Abuse Treatment (no. = 18) in croatia. Methods. Maslach Burnout Inventory was used which measured three burnout dimensions: emotional exhaustion, depersonalization and personal accomplishment; and questionnaire of internal and external burnout factors. Results. The higher levels of emotional exhaustion and depersonalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…and some external factors, e.g., poor work organization, inadequate preparation for concrete work, lack of organizational support, professional isolation, etc. Internal factors include feelings about themselves and about job (see, e.g., Tatalović Vorkapić & Mustapić, 2012).…”
Section: Reasons For Burnout Appearance In Companiesmentioning
confidence: 99%
“…and some external factors, e.g., poor work organization, inadequate preparation for concrete work, lack of organizational support, professional isolation, etc. Internal factors include feelings about themselves and about job (see, e.g., Tatalović Vorkapić & Mustapić, 2012).…”
Section: Reasons For Burnout Appearance In Companiesmentioning
confidence: 99%
“…A high level of burnout has been found among substance abuse counsellors, which can be attributed to a wide range of internal and external factors such as emotions, personality traits, work conditions, and work organisation (Vorkapić & Mustapić, 2012). It has also been reported that counselling professionals are prone to develop three classic burnout symptoms: emotional exhaustion, depersonalisation and reduced personal accomplishment, especially are handling clients with substance abuse problems (Bakker et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that counselling professionals are prone to develop three classic burnout symptoms: emotional exhaustion, depersonalisation and reduced personal accomplishment, especially are handling clients with substance abuse problems (Bakker et al, 2001). Although some studies disclosed that a high level of self-consciousness and mindfulness could help counsellors buffer the negative effects of working with traumatic clients (Ender et al, 2019;Gutierrez & Mullen, 2016;Hardiman & Simmonds, 2013), many other studies showed that a high degree of empathetic demand and frequent exposure to clients could significantly create perfect conditions for occupational hazards (Baldwin-White, 2016;Vorkapić & Mustapić, 2012)…”
Section: Introductionmentioning
confidence: 99%